Digital Thoracic Drainage System: A New Tool For Pediatric Thoracic Surgery - Vasconcelos-Castro, Sofia (2023)
Introduction: Digital thoracic drainage systems usage in pediatrics is underreported, making current recommen- dations based on those for adults. We aim to review our experience on the use of this digital system and to evaluate the adequacy of those recommendations. Methods: Retrospective analysis of patients in whom digital thoracic drainage system was used. All patients were submitted to thoracoscopic bleb/apical lung resection for primary spontaneous pneumothorax. Initially patients were man- aged using the few existing recommendations for children, but after 2 unsuccessful cases we changed our approach into tube clamping after continuous air leak < 5mL/min for at least 24 hours. Results: Seventeen procedures (median 17.2-years) were performed; there were no intraoperative complications. After changing the air leak target, 11 procedures were consecutively managed without complications; the median number of chest radiographs per procedure was 3.0 and the median number of days with chest tube was 4.0 days. Conclusions: This is the first report on the usage of this system in children in Portugal. This system constitutes an important technological innovation, but it needs more data gathering and prospective trials in order to maximize its use in children. The authors suggest an algorithm for the management of thoracic digital drainage in children: removal of chest tubes when the air leak is <5mL/min for 24 hours and to perform chest tube clamping for a minimum of 6 hours before removal.